1996
DOI: 10.1002/(sici)1096-8628(19960102)61:1<21::aid-ajmg4>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Duplication of 7p: Further delineation of the phenotype and restriction of the critical region to the distal part of the short arm

Abstract: We report on a patient with duplication of 7p15→pter and review the literature. Patients with partial duplication of the distal 7p, including only the distal segment 7p15→pter, have a syndrome comparable to that of patients with a larger or complete duplication of 7p. This suggests that the critical region for the dup(7p) phenotype is restricted to 7p15→pter. The complete clinical phenotype of dup(7)(p15→pter) includes mental retardation, skull anomalies, large anterior fontanel, cardiovascular defects, joint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Our final interpretation of the CCR in the mother is as follows: ins(2;7)inv (7) Through the use of the BAC clone panel, the chromosome abnormality in our patient was conclusively identified as a partial trisomy of the short arm of chromosome 7 (7p12.237p21.3). Full or partial trisomy (duplication) 7p has been reported previously in 47 cases (for recent reviews see Cai et al, 1999;Pallotta et al, 1996;Reish et al, 1996;Lurie et al, 1995;Schaefer et al, 1995). 4 -8 Although the extent of the duplication varies among patients, a characteristic phenotype has emerged.…”
Section: Discussionmentioning
confidence: 96%
“…Our final interpretation of the CCR in the mother is as follows: ins(2;7)inv (7) Through the use of the BAC clone panel, the chromosome abnormality in our patient was conclusively identified as a partial trisomy of the short arm of chromosome 7 (7p12.237p21.3). Full or partial trisomy (duplication) 7p has been reported previously in 47 cases (for recent reviews see Cai et al, 1999;Pallotta et al, 1996;Reish et al, 1996;Lurie et al, 1995;Schaefer et al, 1995). 4 -8 Although the extent of the duplication varies among patients, a characteristic phenotype has emerged.…”
Section: Discussionmentioning
confidence: 96%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] Common features include craniofacial anomalies, a large fontanelle, dysmorphism and psychomotor delay, with hypotonia being the most common complication observed. [1][2][3][4][5][6][7][8]10,11,13 In their review of the literature, Cai et al found that 50% of 7p duplications were the result of balanced reciprocal translocation carriers. 3 Reish et al suggested that these could be an entire duplication duplication.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 The critical region for physical and mental abnormalities is 7p15-pter; 2 for craniofacial dysmorphism, it is 7p21. 2,3,9 Both these patient groups, viz. those with physical and mental abnormalities, have many specific features in common.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 7p duplications often result from malsegregation of parental balanced translocations [4,37]. In these patients, poor prognosis quo ad vitam was associated with cardiovascular malformations [1,11,25].…”
Section: Introductionmentioning
confidence: 99%